2007
DOI: 10.1111/j.1468-1331.2007.01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Low RLS prevalence and awareness in central Greece: an epidemiological survey

Abstract: Restless legs syndrome (RLS) is a sensorimotor disorder with a general population prevalence of 3-10%. A single, previous epidemiological study performed in south-east Europe reported the lowest prevalence rate amongst European countries. We conducted a population-based survey of RLS in central Greece. A total of 4200 subjects were randomly recruited. We used the international RLS study group criteria for diagnosis and the severity scale for severity assessment in subjects with RLS. We also included questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
2
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 27 publications
5
62
2
10
Order By: Relevance
“…Relatively few studies have specifically examined the association of RLS to socioeconomic indices, including education, income, and employment, and even fewer have assessed the relation of RLS to race/ ethnicity or marital status. 1,43 In this investigation, participants with RLS were less likely to be college educated and more likely to be lower income, in agreement with some, 20,21,23 but not other studies 21,44,45 in the general population. Likewise, in agreement with a state-wide survey study of 1,803 Kentucky residents, 21 but in contrast to findings from a second large…”
Section: Discussionsupporting
confidence: 87%
“…Relatively few studies have specifically examined the association of RLS to socioeconomic indices, including education, income, and employment, and even fewer have assessed the relation of RLS to race/ ethnicity or marital status. 1,43 In this investigation, participants with RLS were less likely to be college educated and more likely to be lower income, in agreement with some, 20,21,23 but not other studies 21,44,45 in the general population. Likewise, in agreement with a state-wide survey study of 1,803 Kentucky residents, 21 but in contrast to findings from a second large…”
Section: Discussionsupporting
confidence: 87%
“…RLS prevalence has been reported to be higher in female patients in most reports (24,25) and to increase with age (19). Ethnic variations have been described and lower prevalence rates have been claimed in Greeks (27). A recent population-based study has shown a prevalence of 7.1% among Brazilians (28).…”
Section: Discussionmentioning
confidence: 99%
“…This population consisted of all patients with end-stage renal disease who were receiving chronic HD treatment (≥2 times per week for at least 3 months), in six renal units in Greece between January and September 2010. In a previous crosssectional survey of our group [11], conducted by means of standard methodology [19][20][21], we assessed the prevalence and severity of RLS in this population. Briefly, the local version of the four essential clinical criteria of the International Restless Legs Syndrome Study Group (IRLSSG) rating scale, which has been validated in previous studies, was implemented as a screening tool for RLS diagnosis [11,20].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous crosssectional survey of our group [11], conducted by means of standard methodology [19][20][21], we assessed the prevalence and severity of RLS in this population. Briefly, the local version of the four essential clinical criteria of the International Restless Legs Syndrome Study Group (IRLSSG) rating scale, which has been validated in previous studies, was implemented as a screening tool for RLS diagnosis [11,20]. In cases that fulfilled all four criteria, diagnosis was confirmed, and RLS severity was evaluated according to the IRLSSG rating scale (Greek version) during a personal interview conducted by an RLS expert (G.M.H.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation